Activation of GIPR Exerts Analgesic and Anxiolytic-Like Effects in the Anterior Cingulate Cortex of Mice - Wang, Xin-shang; Jiang, Yong-li; Lu, Liang; Feng, Ban; Ma, Xue; Zhang, Kun; Guan, Shao-yu; Yang, Le; Fan, Qing-yu; Zhu, Xiao-chen; Yang, Fan; Qi, Jing-yu; et al. (Frontiers in Endocrinology, 2022)
Background: Chronic pain is defined as pain that persists typically for a period of over six months. Chronic pain is often accompanied by an anxiety disorder, and these two tend to exacerbate each other. This can make the treatment of these conditions more difficult. Glucose-dependent insulinotropic polypeptide (GIP) is a member of the incretin hormone family and plays a critical role in glucose metabolism. Previous research has demonstrated the multiple roles of GIP in both physiological and pathological processes. In the central nervous system (CNS), studies of GIP are mainly focused on neurodegenerative diseases; hence, little is known about the functions of GIP in chronic pain and pain-related anxiety disorders. Methods: The chronic inflammatory pain model was established by hind paw injection with complete Freund’s adjuvant (CFA) in C57BL/6 mice. GIP receptor (GIPR) agonist (D-Ala2-GIP) and antagonist (Pro3-GIP) were given by intraperitoneal injection or anterior cingulate cortex (ACC) local microinjection. Von Frey filaments and radiant heat were employed to assess the mechanical and thermal hypersensitivity. Anxiety-like behaviors were detected by open field and elevated plus maze tests. The underlying mechanisms in the peripheral nervous system and CNS were explored by GIPR shRNA knockdown in the ACC, enzyme-linked immunosorbent assay, western blot analysis, whole-cell patch-clamp recording, immunofluorescence staining and quantitative real-time PCR. Results: In the present study, we found that hind paw injection with CFA induced pain sensitization and anxiety-like behaviors in mice. The expression of GIPR in the ACC was significantly higher in CFA-injected mice. D-Ala2-GIP administration by intraperitoneal or ACC local microinjection produced analgesic and anxiolytic effects; these were blocked by Pro3-GIP and GIPR shRNA knockdown in the ACC. Activation of GIPR inhibited neuroinflammation and activation of microglia, reversed the upregulation of NMDA and AMPA receptors, and suppressed the enhancement of excitatory neurotransmission in the ACC of model mice. Conclusions: GIPR activation was found to produce analgesic and anxiolytic effects, which were partially due to attenuation of neuroinflammation and inhibition of excitatory transmission in the ACC. GIPR may be a suitable target for treatment of chronic inflammatory pain and pain-related anxiety.